Advancing executive coaching : setting the course for successful leadership coaching - Hernez-Broome, Gina.; Boyce, Lisa A. (San Francisco : Jossey-Bass, 2011)
"For anyone who coaches leaders, this book addresses the most critical issues impacting the future of leadership coaching as an organizational development initiative. It is organized around a Leadership Coaching Framework that employs a systems approach to frame the myriad issues. In addition to the introductory chapter that provides an overview of the book, the sixteen contributed chapters are grouped into three sections with the final chapter providing a review of the major themes in the volume with a discussion integrating the global discussions and future directions for leadership coaching"--
Foreword / Allen I. Kraut -- Preface / Gina Hernez-Broome and Lisa A. Boyce -- The Editors. -- The Contributors -- Introduction: State of Coaching: Framing Leadership Coaching Issues / Lisa Boyce and Gina Hernez-Broome -- Section I. Your Traveling Companions: Coach, Client, and Organizational Issues -- 1. Activating the Active Ingredients of Leadership Coaching / Sandra L. Davis and Douglas McKenna -- 2. The Coach: Ready, Steady, Go! / Brian O. Underhill -- 3. Learning to Coach Leaders / Robert J. Lee and Michael H. Frisch -- 4. Good to Great Coaching: Accelerating the Journey / David B. Peterson -- 5. The Client: Who Is Your Coachee and Why Does It Matter? / Anna Marie Valerio and Jennifer J. Deal -- 6. Maximizing Impact: Creating Successful Partnerships Between Coaches and Organizations / Erica Desrosiers and David H. Oliver -- Section II. The Journey: Processes and Practices of Leadership Coaching. -- 7. Building the Coaching Alliance: Illuminating the Phenomenon of Relationship in Coaching / Travis Kemp -- 8. Coaching Programs: Moving Beyond the One-on-One / Lorraine Stomski, Janis Ward, and Mariangela Battista -- 9. Ethics in Coaching / Jonathan Passmore and Lance Mortimer -- 10. Tools & Techniques: What's in Your Toolbox? / Ann M. Herd and Joyce E.A. Russell -- 11. E-Coaching: Accept it, It's Here, and It's Evolving! / Lisa A. Boyce and David Clutterbuck -- Section III.?Recalculating? Directions: Evaluating the effectiveness of Leadership Coaching. -- 12. Evaluating the Effectiveness of Coaching: A Focus on Stakeholders, Criteria, and Data Collection Methods / Katherine Ely and Stephen J. Zacarro -- 13. Evaluating the ROI of Coaching: Telling a Story Not Just a Producing a Number / Merrill C. Anderson -- 14. The Coaching Impact Study?: A Case Study in Successful Evaluation / Derek Steinbrenner and Barry Schlosser -- 15. What Clients Want: Coaching in Organizational Context / Douglas Riddle and Natalie Pothier --16. New Directions: Perspective on Current and Future Leadership Coaching Issues / Paul Tesluk & Jeff Kudish -- Appendix A: Examples of Coaching Frameworks -- Appendix B: Examples of Coaching Techniques. -- Appendix C: Examples of Coaching Assessment Tools -- Appendix D: Sample Individual Development Plan -- Name Index -- Subject Index.
Includes bibliographical references and indexes.
Print version record.
English.
John Wiley and Sons
Keywords: Executive coaching; Accompagnement de gestionnaires; BUSINESS & ECONOMICS -- Workplace Culture; BUSINESS & ECONOMICS -- Corporate Governance; BUSINESS & ECONOMICS -- Leadership; BUSINESS & ECONOMICS -- Organizational Development; Executive coaching